Estudo de efetividade de intervenção psicológica de apoio na prevenção de sintomas de Transtorno de Estresse Pós-Traumático em pacientes submetidos à sedação e internados em Unidade de Terapia Intensiva - Caiuby, Andrea Vannini Santesso [UNIFESP] (2010)
Goal: To evaluate the effectiveness of support psychological intervention in the prevention of Posttraumatic Stress Disorder (PTSD) in intensive care unit (ICU) sedated patients. Method: Randomized controlled clinical trial (treatment group – G1 and control group – G2). Adult sedated patients in ICU for more than 24 hours and with a history of delusional memories were allocated. The psychological support intervention was based on psychodynamic theory and on cognitive-behavioral techniques, being administered in the ICU. Date regarding the demographic profile, clinical history before commitment, primary traumatic events and actual commitment of patients were collected. After the return of consciousness, the following assessment tools were administered: Care Unit Memory Tool and the Hospital Anxiety and Depression Scale (HADS) – time 1 (after ICU discharge); Impact Event Scale – Revised (IES-R), Bond´s Defense Style Questionnaire and HADS – time 2 (12 weeks after the return of consciousness) and in time 3 (24 weeks after the return of consciousness). Results: The sample was constituted of 11 patients in G1 and 10 patients in G2. Significant differences between groups were found in regard to the use of anxiolytic in the ICU (p=0.01) and to the intensity of some defensive mechanisms: inhibition (p=0.01), omnipotence (p=0.04) and annulation (p=0.001). The analysis regarding the effects of these variables in the results of the IES in time 3 showed that only omnipotence interfered and treatment group displayed superior means. Conclusion: The psychological intervention was not effective at the end of six months, therefore the indication of such intervention in the context of ICU is not recommended. It is worth of note that the anxiogenic character of the administered intervention is an important variable in the understanding of results and the defense omnipotence is regarded as a protective factor for the development of PTSD symptomatology. Therefore, new studies related to the effectiveness of psychological intervention in ICU for the prevention of PTSD must consider the configuration of psychological phenomenon taking into account the complexity of variables affecting specific clinical contexts.